GRAMMATICAL CATEGORIES EXPRESSING FUTURE TIME IN UZBEK AND ENGLISH LANGUAGES - Furkatova Makhliyo (International Journal of Literature and Language Studies, 2026)
This article examines the grammatical categories used to express future time in the Uzbek and English languages. Future time is an important grammatical concept that enables speakers to refer to actions, events, and situations that will occur after the moment of speaking. The study explores the morphological and syntactic means employed in both languages to indicate future actions. In Uzbek, future time is primarily expressed through specific verb forms and affixes, whereas in English it is conveyed through a variety of grammatical structures, including modal auxiliaries, tense forms, and periphrastic constructions. By comparing these mechanisms, the article identifies both similarities and differences in the expression of futurity. The findings demonstrate that while both languages possess effective means of expressing future time, they differ significantly in their grammatical organization and usage patterns. The comparative analysis contributes to a deeper understanding of the linguistic features of Uzbek and English and provides useful insights for language learners, translators, and researchers in the field of comparative linguistics.